2020
DOI: 10.3390/genes11070829
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Genetic and Epigenetic Alterations of BARD1 on the Development of Non-Breast and Non-Gynecological Cancers

Abstract: Breast Cancer 1 (BRCA1) gene is a well-characterized tumor suppressor gene, mutations of which are primarily found in women with breast and ovarian cancers. BRCA1-associated RING domain 1 (BARD1) gene has also been identified as an important tumor suppressor gene in breast, ovarian, and uterine cancers. Underscoring the functional significance of the BRCA1 and BARD1 interactions, prevalent mutations in the BRCA1 gene are found in its RING domain, through which it binds the RING domain of BARD1. BARD1-BRCA1 het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 146 publications
(257 reference statements)
2
14
0
Order By: Relevance
“…Our study also proposes BARD1 as a prognostic gene in stage IV ovarian cancer. BARD1 , BRCA1‐associated RING domain 1, acts as a tumor suppressor gene and its interaction with BRCA1 is essential for the tumor suppression activity of BRCA1 34 . In our study, the AA and AG genotypes of rs16852804 (G>A) in BARD1 were associated with shorter OS.…”
Section: Discussionsupporting
confidence: 48%
“…Our study also proposes BARD1 as a prognostic gene in stage IV ovarian cancer. BARD1 , BRCA1‐associated RING domain 1, acts as a tumor suppressor gene and its interaction with BRCA1 is essential for the tumor suppression activity of BRCA1 34 . In our study, the AA and AG genotypes of rs16852804 (G>A) in BARD1 were associated with shorter OS.…”
Section: Discussionsupporting
confidence: 48%
“…Several lines of evidence from genome-wide association studies (GWAS) in neuroblastomas have identified predisposing SNPs in BARD1 (BRCA1-associated RING domain1), which is a potent interacting protein of BRCA1. As the BRCA1-BRAD1 complex has been implicated in initiating DNA end resection and promoting RAD51 loading in HR [ 56 , 57 ], it remains unclear what the direct roles of BRCA1 and the other mediators of DDR are in neuroblastoma pathogenesis. Importantly, BRCA1-deficient tumors are critically dependent on abrogation of p53 function in mice and humans, suggesting that the combination of DDR deficiency and loss-of-function p53 is highly susceptible for tumorigenesis.…”
Section: “Accelerating” the Cell Cycle To Induce Catastrophic Cell Deathmentioning
confidence: 99%
“…Regulation of alternative splicing process by H3K36me3 reduced BARD1 expression with subsequent suppression of ATM/ATR signaling that regulates hESC differentiation [ 47 ]. Another report revealed that in patients with hepatocellular carcinoma (HCC) that ended by the cirrhotic liver, the BARD1 gene showed significant hypomethylation (13.3%) in comparison to normal controls BARD1 hypomethylation was suggested as a predictive biomarker for predisposing to aggressive disease in HBV-negative patients [ 48 ].…”
Section: Introductionmentioning
confidence: 99%